Thermal decomposition and desorption of PFPE Zdol on a DLC substrate using quartic bond interaction potential. Issue 85 (16th September 2015) - Deb Nath, S. K.
<x xml:space="preserve">Abstract</x> In heat assisted magnetic recording (HAMR) system, heating of the hard disk magnetic layer is carried out by applying laser rays during the movement of the read/write head over the carbon overcoat for the purpose of reading and writing on its magnetic layer.